Human Brain Stem Structures Respond Differentially to Noxious Heat - Ritter, Alexander; Franz, Marcel; Dietrich, Caroline; Miltner, Wolfgang H.; Weiss, Thomas (Frontiers in Human Neuroscience, 2013)
Concerning the physiological correlates of pain, the brain stem is considered to be one core region that is activated by noxious input. In animal studies, different slopes of skin heating (SSH) with noxious heat led to activation in different columns of the midbrain periaqueductal grey (PAG). The present study aimed at finding a method for differentiating structures in PAG and other brain stem structures, which are associated with different qualities of pain in humans according to the structures that were associated with different behavioral significances to noxious thermal stimulation in animals. Brain activity was studied by fMRI in healthy subjects in response to steep and shallow SSH with noxious heat. We found differential activation to different SSH in the PAG and the rostral ventromedial medulla (RVM). In a second experiment we demonstrate that the different SSH were associated with different pain qualities. Our experiments provide evidence that brainstem structures, i.e. the PAG and the RVM, become differentially activated by different SSH. Therefore, different SSH can be utilized when brain stem structures are investigated and when it is aimed to activate these structures differentially. Moreover, percepts of first pain were elicited by shallow SSH whereas percepts of second pain were elicited by steep SSH. The stronger activation of these brain stem structures to SSH, eliciting percepts of second vs. first pain, might be of relevance for activating different coping strategies in response to the noxious input with the two types of SSH.